The san peregrino landslide, in the autopista del cafe - Estrada-Trujillo, Walter Leonin; Jaramillo-Correa, Fabio; Naranjo-Henao, José Luis (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2010)
The “Autopista del Café” in the stretch comprehended between the cities of Manizales and Pereira showssome unstable geological sites who has demanded great money expenses for stabilization. One of them iscalled “San Peregrino”, located at abscissa K7+630 of the roadway Manizales-Pereira. The road in this sector pass along a ridge water divide about 20 meters wide on top, an manifests severe geological stability problems toward both sides of ridge.. The water divide is constituted by thick beds of black shales which are interstratified with thin beds of chert of centimetric dimensions, disposed in the form of a fold with its axis oriented along the water divide. The zone is affected by the Fundamental Romeral Fault causing high fracturation grade in cherts beds, gravity folds in the shales and complex superimposed folds in all the sequence, characteristhics that together with high flow of underground water, have caused stability problems in the area with the consequent demand of a high inversion in stabilization works. The implemented stabilization works until now, are superficial and subterranean drainage, and several aligned caissons to protect the highway floor.